The Deep Understanding into the Promoted Carbon Dioxide Electroreduction of ZIF‐8‐Derived Single‐Atom Catalysts by the Simple Grinding Process. Issue 7 (29th April 2022) - Chen, Zhangsen; Zhang, Gaixia; Hu, Qingmin; Zheng, Yi; Cao, Siyi; Chen, Guozhu; Li, Cuncheng; Boyko, Teak; Chen, Ning; Chen, Weifeng; Regier, Tom; Dynes, James; et al.
Abstract : Zeolitic imidazolate framework (ZIF‐8)‐derived single‐atom catalysts (SACs) are widely studied in many catalytic reactions such as hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), and CO2 reduction reactions (CO2 RR). Grinding procedures involved in the synthesis of ZIF‐8‐derived SACs could affect the catalytic performance but are less evaluated in the literature. Herein, a series of ZIF‐8‐derived cobalt SACs (C–Co–ZIFs) with different grinding processes to investigate the impact of the grinding degrees on the performance of the electrochemical reduction reaction of CO2 (ECO2 RR) is presented. The moderate grinding process affords a boost in CO Faradaic efficiency (FE, around 15% higher than that of the original C–Co–ZIF) and the highest current densities among all the samples. The variations in the electronic structure of the Co active sites in the ground catalysts are confirmed by X‐Ray absorption spectroscopy (XAS) and X‐Ray emission spectroscopy (XES) for improved catalytic performance. The increased micropores in the moderately ground catalyst provide more exposed active sites while the increased meso‐ and macropores promote the mass transfer, benefiting the ECO2 RR performance. It suggests that the impact of grinding processes on the synthesis of ZIF‐8‐derived SACs should be considered for the evaluation of the catalytic performance. Abstract : A series of ZIF‐8‐derived cobalt single‐atom catalysts (C–Co–ZIF) with different grinding processes are synthesized to investigate the impact of grinding degrees on the performance of the electrochemical reduction reaction of CO2 (ECO2 RR). The moderate grinding process affords the best ECO2 RR performance, due to the modified electronic structure of the Co active sites and the optimized pore structures.